Using the theory of planned behaviour to predict nurse's intention to undertake dual practice in China: A multicentre survey. Issue 11 (11th March 2019) - Bai, Xiaoling; Wang, Anni; Plummer, Virginia; Lam, Louisa; Cross, Wendy; Guan, Ziyao; Hu, Xin; Sun, Mei; Tang, Siyuan
Abstract: Aims and objectives: To identify the intention of nurses to dual practice (DP) and inform policymaking in centralised government settings. Background: DP is pervasive worldwide but was not permitted in China until 2009, with a primary goal of encouraging nurses from over‐staffed health services to work additional shifts in understaffed settings. Design: A descriptive cross‐sectional survey. Methods: A DP questionnaire based on the theory of planned behaviour was developed and issued to nurses from three comprehensive public hospitals in 24 units selected by stratified random cluster sampling ( n  = 526). This study was reported based on STROBE checklist. Results: The mean for intention was 3.47 with strongly disagree as one point, neutral as three point and strongly agree as five point in scaling. Nurses with any of these characteristics: female, aged between 40 and 49, married, working more than 15 years, and managers were significantly reluctant to undertake DP. The structural equation model showed that the level of positive attitude, subjective norm and perceived behavioural control could positively predict intention, and attitude had highest effect value. Perceived behavioural control and attitude acted as sequential mediators between subjective norm and intention. Nurses preferred large or private hospitals if conducting DP without restriction from the government. Conclusions: Nurses' intention to undertake DP was not strong, which was impacted by attitude, subjective norm, time and energy. Nurses preferred large or private hospitals; therefore, the goal of improving equity by DP in developing countries might be undermined. Relevance to clinical practice: To encourage DP, attitude and subjective norm are important paths, the latter being the initial step. Reasonable incentives or restrictions, such as specifying regulations on practice place and time limitation, qualifications and legal liability and remuneration are recommended to ensure successful DP implementation from over‐staffed health services to understaffed settings.